The Potential of Thiolated Polymers for Peptide Drug Delivery - Jitendra Kawadkar, Jitendra Kawadkar (International Journal of Pharmaceutical & Biological Archive, 2010)
Thiolated polymers are generated by the immobilisation of thiol-bearing ligands to mucoadhesive polymeric excipients. The mucoadhesive properties of these polymers are improved up to 130-fold by formation of disulfide bonds with mucus glycoproteins. Due to formation of inter and intramolecular disulfide bonds within the thiolated polymer itself, tablets, microparticles or in situ gelling formulations display strong cohesive properties resulting in comparatively higher stability, prolonged disintegration times and a more controlled release of peptide drug. Peptide drug permeation through mucosa can be improved by the use of thiolated polymers. Thiolated polymers also exhibit improved inhibitory properties towards peptidases. The efficacy of thiolated polymers in peptide drug delivery could be demonstrated by various in vivo studies. In different studies, formulations comprising the corresponding unmodiï¬ed polymer had only a marginal or no effect. The results of the studies prove that thiolated polymers have potential for peptide drug delivery. Keywords: Thiolated polymers, Peptide drug delivery, Mucoadhesion and cohesion, Permeation enhancement, Enzyme inhibition, Controlled drug delivery, Stability of thiolated polymers